From integrative bioethics to integrative bioethics: European and American perspectives - Rinčić, Iva (Journal international de bioéthique et d'éthique des sciences, 2016)
The questions confronting integrative bioethics have been emerging, revealing not only different definitions, but also perspectives and approaches (Jurić, 2007; Schaefer-Rolffs, 2012; Bracanović, 2012; ten Have, 2012; Muzur, 2012). From those conceptual ambiguities, a new moment in the history and methodology of integrative bioethics has emerged as well, thus shaping not one, but two approaches to integrative bioethics, one from Europe (Croatia), and another from United States of America (Tuskegee, Alabama). In this article, the authors will try to analyse the two mentioned approaches. Sharing the same name, but differing in their roots, methodology and aims, those two approaches to integrative bioethics will be used as starting points in the authors’ attempt to answer the question of whether the differences observed can also serve as binding elements. In other words, once again, bioethics has been creatively used as a bridge over the tormented reality of life activities.